Breve storia del telerilevamento da satellite in Italia e in Europa - Quaglione, Giuseppe (GEOmedia, 2009)
Brief history of satellite remote sensing in italy and europe After a short introduction on the very first satellites for meteorological applications and for earth observation in the 60's and 70's, attention is called on the need for parallel development of adequate earth segment installations and human resources for the interpretation of data gathered by the satellites in various possible applications. Therefore the article is structured in two main sections, one on the space segment and another on the earth segment historical developments.